Software Engineering / Principles and Practice Second Edition - Vliet Van Hans (John Wiley & Sons, Ltd, 2002)
This book challenges the reader to appreciate the issues, design trade offs and teamwork required for successful software development. Preface, Introduction, Software Management, Configuration Management, On Managing Software Quality, Cost Estimation, The Software Life Cycle, Software Architecture, Software Testing, Supporting Technology, User Interface Design, Software Tools, Bibliography, Index.